2014
DOI: 10.1038/cddis.2014.142
|View full text |Cite
|
Sign up to set email alerts
|

MARCH5-mediated quality control on acetylated Mfn1 facilitates mitochondrial homeostasis and cell survival

Abstract: Mitochondrial dynamics and quality control have a central role in the maintenance of cellular integrity. Mitochondrial ubiquitin ligase membrane-associated RING-CH (MARCH5) regulates mitochondrial dynamics. Here, we show that mitochondrial adaptation to stress is driven by MARCH5-dependent quality control on acetylated Mfn1. Under mitochondrial stress conditions, levels of Mfn1 were elevated twofold and depletion of Mfn1 sensitized these cells to apoptotic death. Interestingly, overexpression of Mfn1 also prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 41 publications
3
89
0
Order By: Relevance
“…Furthermore, in Mfn1 knockout cells, more mitochondrial DNA (mtDNA) mutations were observed32. By contrast, overexpression of Mfn1 by transient transfection of cultured cells contributed to the formation of mitochondrial networks, whereas a point mutation in the Mfn1 gene resulted in dramatically attenuated mitochondrial fusion31. All these findings indicate that Mfn1 plays a key role in mitochondrial fusion machinery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in Mfn1 knockout cells, more mitochondrial DNA (mtDNA) mutations were observed32. By contrast, overexpression of Mfn1 by transient transfection of cultured cells contributed to the formation of mitochondrial networks, whereas a point mutation in the Mfn1 gene resulted in dramatically attenuated mitochondrial fusion31. All these findings indicate that Mfn1 plays a key role in mitochondrial fusion machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that Mfn1 was broadly expressed in different tissues and at high levels30. Lack of Mfn1 leads to fusion deficiency and results in severely fragmented mitochondria31. Furthermore, in Mfn1 knockout cells, more mitochondrial DNA (mtDNA) mutations were observed32.…”
Section: Discussionmentioning
confidence: 99%
“…195 In antimycin A-treated cells, the Mitofusin-1 level is markedly increased with augmented cell death. Antimycin-A is a complex III inhibitor that is used to increase ROS production from from the Qo site of complex III, 122 favoring ROS production in a similar manner to the age-related defect discussed above.…”
Section: Mitochondrial Fission and Fusionmentioning
confidence: 99%
“…Assessing a potential link between March5 activity and mitochondrial morphology or function is complicated as experimental inactivation of March5 promotes conflicting phenotypes. For example, March5 knockdown [56] or expression of the March5 H43W -RING mutant results in elongated, hyperfused mitochondria [55*,57], which antagonizes mitochondrial stress-induced apoptosis [57,58]. By contrast, March5 knockout cells displays fragmented mitochondria [59,60*], and accordingly, are more sensitive to apoptotic insults [60*].…”
Section: Ubiquitin Ligases As Emerging Regulators Of Mitochondrial Dymentioning
confidence: 99%